Investor sentiment, misreaction, and the skewness‐return relationship - Chen, Chin‐Ho (The journal of futures markets, 2021)
This study examines the effect of investor sentiment on misreaction and explores the time‐series relationship between risk‐neutral skewness (RNS) and subsequent stock market returns contingent on sentiment‐induced overreaction. Using the adjusted put‐call implied volatility spread as a misreaction proxy and Bakshi et al.'s method to measure RNS, we find that pessimism leads to overreaction. This overreaction could strengthen the negative RNS‐return relationship, with higher market returns following lower RNS. Our results are robust even after excluding the sample period of the 2008 financial crisis, profiting from market‐timing strategies based on the levels of RNS and overreaction, and using an alternative RNS measure.